Pseudomonas eucalypticola sp. nov., a producer of antifungal agents isolated from Eucalyptus dunnii leaves - Yujing Liu (Nature Portfolio, 2021)
Abstract Pseudomonas are ubiquitously occurring microorganisms and are known for their ability to produce antimicrobials. An endophytic bacterial strain NP-1 T, isolated from Eucalyptus dunnii leaves, exhibits antifungal properties against five tested phytopathogenic fungi. The strain is a Gram-negative rod-shaped bacterium containing a single polar flagellum. It is strictly aerobic, grows at 4–37 °C, 2–5% NaCl, and pH 3–7. The 16S rRNA sequence analysis showed that NP-1 T belongs to the Pseudomonas genus. Phylogenetic analysis based on four concatenated partial genes (16S rDNA, gyrB, rpoB and rpoD) and the phylogenomic tree indicated that NP-1 T belongs to Pseudomonas fluorescens lineage but is distinct from any known Pseudomonas species. The G + C mol % of NP-1 T genome is 63.96, and the differences between NP-1 T and related species are larger than 1. The digital DNA-DNA hybridization and tetranucleotide signatures are 23.8 and 0.97, which clearly separates strain NP-1 T from its closest neighbours, Pseudomonas coleopterorum and Pseudomonas rhizosphaerae. Its phenotypic and chemotaxonomic features confirmed its differentiation from related taxa. The results from this polyphasic approach support the classification of NP-1 T as a novel species of Pseudomonas, and the name of Pseudomonas eucalypticola is thus proposed for this strain, whose type is NP-1 T (= CCTCC M2018494T = JCM 33572 T).